Leadership styles and employees' performance: A case of family-owned manufacturing company, Cape Coast - Amegayibor, Godson Kwame (Goodwood Publishing, 2021)
Purpose: This study aimed to explore the association between leadership styles and employee performance in a family-owned manufacturing business. Research methodology: For data translation and analysis, the study used a quantitative approach and a correlational design, a census technique of sampling 400 employees, an interview schedule, multiple linear regression, and the Statistical Package for Social Sciences (SPSS) 16.0 Versions. Results: Results revealed that autocratic, charismatic, and paternalistic leadership styles influence employees' performance. The result also revealed that autocratic, charismatic, and visionary leadership styles influence error reduction. Again the result shows that paternalistic and visionary leadership styles influence employees' quality of work. Limitations: The study's main weakness is that it only looked at nine specific leadership styles and their effects on employee performance. Contribution: Given this, managers should consider using leadership styles with stronger predictions in a given situation to drive employees' performance, reduce employees' errors in work and enhance employees' quality of work.